Economic empowerment of Moroccan women: an analysis using Amartya Sen’s capabilities approach - EL HAMIDI, Nabil; ED-DIB, Mohamed (Revue Internationale du Chercheur, 2020)
This paper analyzes the determinants of the economic empowerment of Moroccan women by relying on Amartya Sen’s capability approach, which emphasizes a multidimensional vision of development centered on individuals’ real freedoms. The study explores three key dimensions: individual capabilities, the socio-economic environment, and social inclusion. Through an empirical analysis based on a Tobit model, it evaluates the impact of several factors such as education, equal opportunities, access to productive resources, and public policies on women’s economic autonomy. The sample of 264 Moroccan women, representative of geographical and socio-economic diversity, enabled an analysis of the interactions between explanatory variables (education, structural barriers, rights, economic participation, etc.) and the dependent variable measuring economic empowerment. The results show that access to education, the reduction of structural barriers, equal opportunities, favorable public policies, and improved living conditions have a significant and positive effect on women’s empowerment. Conversely, access to financing and active participation in economic decision-making did not demonstrate a significant impact. The study highlights the importance of strategic investments in education, infrastructure, and institutional reforms to strengthen women’s economic empowerment. It also calls for coordinated efforts between public, private, and civil society actors to overcome systemic barriers and build an inclusive and equitable society.